LAYANAN BIMBINGAN DAN KONSELING DALAM MOTIVASI BELAJAR BAGI SISWA SMK N 3 KASIHAN BANTUL YOGYAKARTA - Isna Wahyu Hidayati (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2020)
Low learning motivation is very influential on school achievement. Motivation is a factor for students because it can support the spirit of learning. The benefits of learning motivation are very much like enthusiasm in completing schoolwork, student achievement increases, and fosters confidence. This study aims to determine counseling guindance services in learning motivation for students of SMK N 3 Kasihan Bantul. This research uses a descriptive qualitative approach. The results of this study resulted in the services provided by BK teacher including all students both students with special needs or not, because the scholl of SMK N Kasihan accepts students with special needss, there are 4 classifications of children with special needs in SMK N Kasihan namely slow learners, autistic, deaf, tunadaksa. The counseling guidance for students of SMK N 3 Kasihan is first, at the beginning of the semester the guidance teacher chooses and sorts and looks for students who have decreased learning, can be seen from the daily grades or report cards. Second, provide special hours when there are empty subjects because the teacher does not have special hours to enter the class because there are too many subjects that require a lot of time such as the practice of drawing, painting and photographing. Third, BK teachers work together with the homeroom teacher or other teachers to find out the problems experienced by students.whereas counseling guindance service at SMK N 3 Kasihan, BK teacher guidance service condacted by BK teacher are orientation services, information service, indicidual counseling services, group guidance services, and group counseling services.